Effect of heat treatments on the germination of Cistus ladanifer L. - Pereira, I.P.; Dias, A.S.; Dias, L.S. (My University, 1993)
Seeds of Cistus ladanifer were subjected to heat treatments by exposure to temperatures ranging from 10 C to 150 C during 15 minutes, and then incubated in controlled conditions. Final germination increased with temperature with an observed maximum at 90 C, decreasing very quickly thereafter, with no germination at 130 C or higher temperatures. In the case of this aromatic shrub the rupture of seed coats could not account for the observed results, because no stimulus in water uptake was found when seeds were subjected to temperatures effective in stimulating final germination. Other hypothesis to explain the assumed adaptation to fire are currently under investigation.
Keywords: fire